Nobiletin Inhibits Cell Viability via the SRC/AKT/STAT3/YY1AP1 Pathway in Human Renal Carcinoma Cells - Wei, Di; Zhang, Geng; Zhu, Zheng; Zheng, Yu; Yan, Fei; Pan, Chongxian; Wang, Zhiyong; Li, Xian; Wang, Fuli; Meng, Ping; Zheng, Wanxiang; Yan, Zhao; et al. (Frontiers in Pharmacology, 2019)
Nobiletin is a polymethoxy flavonoid isolated from Citrus depressa and Citrus reticulata. It has been reported that nobiletin can suppress tumors. We primarily explored the antitumor effects of nobiletin and the associated potential mechanisms in ACHN and Caki-2 renal carcinoma cells. A CCK-8 assay and cloning experiments were used to assess cell viability, and a transwell assay and scratch test were used to assess metastatic ability. The cell cycle was analyzed by flow cytometry, whereas apoptosis was analyzed using flow cytometry and a terminal dexynucleotidyl transferase (TdT)-mediated dUTP nick end labeling (TUNEL) assay. Protein expression was examined by Western blot and immunofluorescence. Renal cancer cells were subcutaneously transplanted into nude mice for in vivo studies. The data showed that nobiletin administration significantly dose- and time-dependently suppressed renal cancer cell proliferation; moreover, nobiletin treatment induced cell cycle arrest in the G0/G1 phase and promoted apoptosis. Immunofluorescence analysis indicated that nobiletin decreased the nuclear localization of signal transducer and activator of transcription 3 (STAT3) and YY1-associated protein 1 (YY1AP1). Western blot showed that the levels of phosphorylated SRC, phosphorylated AKT serine/threonine kinase (AKT), and phosphorylated STAT3 were decreased, whereas that of phosphorylated YY1AP1 was increased. The results further showed that application of insulin-like growth factor 1 (IGF1) was able to reverse the nobiletin-induced changes in the levels of phosphorylated AKT, phosphorylated STAT3, and phosphorylated YY1AP1, and could also reverse the antitumor effects of nobiletin. The results of in vivo experiments showed that, compared to the control, tumor volume and weight were both reduced following nobiletin treatment. In conclusion, our study demonstrated that nobiletin can inhibit renal carcinoma cell viability and provides a novel therapeutic approach for the treatment of kidney cancer.